2016
DOI: 10.15562/bmj.v5i3.222
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication and Contributing Factors: A Questionnaire Survey Among Iranian Households

Abstract: Background: Self-medication is a serious danger in every health sector which potentially brings harmful side effects for the society. The aim of this research was to investigate self-medication and its contributing factors among residents of Yazd province in Iran in 2014. Methods: A descriptive, cross sectional study was conducted in 2014 using a self-constructed questionnaire. A total of 580 families living in Yazd in the time period of study were contributed to fill out the questions organized in two section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The practice of self-treatment has remained a global public health concern (Yadav and Rawal, 2015;Gupta and Singh, 2016;Chang et al, 2017), causing inadequate dosing, incomplete treatment courses, inappropriate usage of medicines and drug resistance (Olumide et al, 2018;Hitesh et al, 2018). The prevalence of self-treatment in Iran has been found to be three times more than global average (Nadia et al, 2016), with the most commonly used medications being analgesics, eye drops, antibiotics, cough and cold preparations, (Saber et al, 2015). Similar studies reported a prevalence of 86.4% in Egypt in 1995 (Agbor and Azobo, 2011;Aashi et al, 2016;Khaled and Haytham, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The practice of self-treatment has remained a global public health concern (Yadav and Rawal, 2015;Gupta and Singh, 2016;Chang et al, 2017), causing inadequate dosing, incomplete treatment courses, inappropriate usage of medicines and drug resistance (Olumide et al, 2018;Hitesh et al, 2018). The prevalence of self-treatment in Iran has been found to be three times more than global average (Nadia et al, 2016), with the most commonly used medications being analgesics, eye drops, antibiotics, cough and cold preparations, (Saber et al, 2015). Similar studies reported a prevalence of 86.4% in Egypt in 1995 (Agbor and Azobo, 2011;Aashi et al, 2016;Khaled and Haytham, 2018).…”
Section: Introductionmentioning
confidence: 99%